The Catholic Church and the Hunger Strikes of Terence MacSwiney and Bobby Sands. Issue 2 (2nd April 2016) - Scull, Margaret M.
Abstract: Differences in the reactions of the Irish Catholic Church to the hunger strikes of Terence MacSwiney and Robert 'Bobby' Sands can be explained through the Church's relationship with the British government. The Church supported MacSwiney's 1920 hunger strike, whereas the tiered hierarchical structure of the Church split in response to Sands' strike in 1981. Two major reasons account for the differing reactions to these protests: the Church's desire to control Irish education in 1920; and the magnification of class and political differences between the Church clergy and hierarchy in 1981. The Church was united in its support of Irish republicanism during MacSwiney's strike. By the late nineteenth century, the British government had ceded most control over Ireland's primary and secondary education to Protestant and Catholic churches. After the signing of the Anglo-Irish Agreement in 1921, when the Free State government gave the Catholic Church even greater autonomy over education, the Church changed its position on hunger striking. During Sands' 1981 strike, many lower-class Irish clergymen, who cared less about British political sensitivities than the hierarchy, sympathised with the hunger strikers' cause. Meanwhile, the Irish and English hierarchies continued to condemn violence and hunger striking.